NLO QCD corrections to WZ + jet production with leptonic decays - Campanario Pallás, Francisco; Englert, Christoph; Kallweit, Stefan; Spannowsky, Michael; Zeppenfeld, Dieter (Journal of high energy physics, 2010)
We compute the next-to-leading order QCD corrections to WZ + jet production at the Tevatron and the LHC, including decays of the electroweak bosons to light leptons with all off-shell effects taken into account. The corrections are sizable and have significant impact on the differential distributions.
Gesehen am 29.03.2023